TECHNICAL EFFICIENCY AND ECONOMIC ANALYSIS OF USAGE PRODUCTION FACTORS OF POTATO FARMING IN NGABLAK SUB-DISTRICT, MAGELANG REGENCY - Septi Putri Hardiyanti; Titik Ekowati; Wiludjeng Roessali (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
This research aims to analyze the effect of the use of production factors on the amount of potato production, as well as to analyze the technical and economic efficiency of the use of potato farming production factors in Ngablak District, Magelang Regency.thesurveymethodwasusedin this research. The research sample was determined byaimplerandom sampling method with the number of respondents as many as 75 potato farmers. The results showed that the production factor of land area, seeds, pesticides, and labor partially had a significant effect on potato farming production, while the production factors of organic fertilizer and phonska fertilizer had no significant effect on potato production in the study area. Potato farming in Ngablak District is not technically efficient with an average technical efficiency value of 0.72. The use of inputs for the production of land areas, seeds, organic fertilizers and pesticides has not yet achieved economic efficiency, while the use of inputs for the production of phonska fertilizer and labor is economically inefficient.